Indonesian Women's Leadership (Quranic Maudhu'i Interpretation of Indonesian Ministry of Religious Affairs) - Azkiyah, Ulfa Mina; Sulaiman, Sulaiman; Hasan, Ilham Ali; Wisnu Wardana, Rizki Afrianto; Izah, Syafira Anisatul (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2022)
AbstractThis article answers how the Maudhu'i Landscape of the Ministry of Religious Affairs of the Republic of Indonesia views women's leadership in Indonesia and implementation in the field. This paper aims to reveal women's leadership in Indonesia from the point of view of interpretation and its implementation in the field. This view is backed by the leadership described in the Qur'an, although in an inappropriate field. Therefore, women's leadership became the object of study in this article. In developing countries such as Indonesia, women's leadership is open but limited by the patriarchy embraced by Indonesian society. This research is descriptive research with a central study approach whose data sources are from the Qur'an, hadith books, journals in the same direction as research, and supporting books. Despite the debate about leadership according to social experts and the sciences related to it, the Qur'an has seriously expounded on leadership itself. The discourse of leadership in the Qur'an aims to find solutions and innovations from the verses to be ideas in human relationships. Leadership is the development of human resources, natural resources, and improvements in the government system so that these three associations can change existing leadership patterns. The Maudhu'i interpretation of the Ministry of Religious Affairs of the Republic of Indonesia has themes that classify women's leadership in the family, women's leadership in worship, women's leadership in society, and women's leadership in the state.Keywords: Al-Qur'an; Maudhu'i Interpretation of Qur’an; Woman leadership. AbstrakArtikel ini menjawab bagaimana Landskap Maudhu’i Kementerian Agama RI memandang kepemimpinan perempuan di Nusantara serta aplikasi dilapangan. Sehingga Tulisan ini bertujuan untuk mengungkap kepemimpinan perempuan di Nusantara dari sudut pandang tafsir dan aplikasi dilapangan. Hal ini dilatar belakangi oleh kepemimpinan yang dijelaskan dalam al-qur’an akan tetapi dilapangan tidak sesuai. sehingga kepermimpinan perempuan menjadi objek kajian artikel ini. Di negara berkembang seperti Indonesia kepemimpinan perempuan terbuka akan tetapi dibatasi oleh paham partiarki yang dianut oleh masyarakat Indonesia. Penelitian ini masuk kedalam klaster penelitian kulitatif diskriptif dengan pendekatan kajian pusataka. Terlepas dari perdebatan tentang kepemimpinan menurut pakar sosial, serta ilmu-ilmu yang berkaitan dengannya, sesunggunya al-Qur’an telah memaparkan tentang kepemimpinan itu sendiri. Diskursus kepemimpinan di dalam al-Qur’an bertujuan untuk menemukan solusi dan inovasi dari ayat-ayat al-Qur’an sehingga menjadi gagasan dalam hubungan antar manusia dengan manusia. Kepermimpinan tersebut adalah pengembangan Sumber Daya Manusia, sumber daya alam dan perbaikan dalam sistem kepemerintahan, sehingga dari tiga soslusi ini mampu merubah pola kepemimpinan yang ada. Seperti yang ada dalam Landskap Maudhu’i Kementerian Agama RI yang mengklasifikasikannya dalam Kepemimpinan Perempuan dalam Keluarga, Kepemimpinan Perempuan dalam Ibadah, Kepemimpinan Perempuan dalam Masyarakat, dan Kepemimpinan Perempuan dalam Negara.Kata Kunci: Al-Qur’an; Kepemimpinan perempuan; Tafsir Maudhu’i.